Maternal consumption of fish oil protected breast-fed piglets against Escherichia coli lipopolysaccharide-induced damage through reshaping of intestinal fatty acids profile - Fang, Bo; Zhao, Lianpeng; Huo, Bin; Chen, Fangyuan; Yuan, Peiqiang; Lai, Shanshan; Wu, Aimin; Zhuo, Yong (Frontiers in Veterinary Science, 2024)
It has been well documented that n-3 polyunsaturated fatty acids (n-3 PUFA) can alleviate inflammation caused by Escherichia coli (E. coli) lipopolysaccharides (LPS), the etiologic agents that causing yellow or white dysentery in young pigs. However, it remains unclear whether the increase in n-3PUFA availability could enhance the ability of nursery pigs to resist invasion by E. coli. LPS. Twenty-four 21-day-old female piglets, each two of them from the same sow fed the beef tallow (BT) or fish oil (FO) diets, were allocated into four treatment groups: BT-CON, piglets from the BT-fed sows and intraperitoneally injected with saline (9 g/L); BT-LPS, piglets from the BT-fed sows and injected with LPS (100 μg/kg body weight); FO-CON, piglets from the FO-fed sows and injected with saline; FO-LPS, piglets from the FO-fed sows and injected with LPS. Following 2h of LPS challenge, the magnitudes of increase in body temperature approached to a marked (P<0.01) difference between the BT-CON and BT-LPS piglets, whereas the dramatic (P<0.01) difference between the FO-CON and FO-LPS piglets was only observed at 4h post LPS challenge. The body temperature averaged across the time points evaluated was about 0.2°C lower (P<0.05) in the FO group than in the BT group. The FO group had lower (P<0.05) mean corpuscular hemoglobin concentration, lower increase in serum interleukin (IL)-1β (P<0.10) and IL-8 (P<0.05) levels, higher (P<0.01) serum albumin concentration, and higher (P=0.10) ratios of jejunum villus height to crypt depth than the BT group. The FO group had much higher (P<0.0001) ileal content of C20:5n3, C24:0, and C22:6n3, which were 2~4 times the content of the BT group. LPS challenge resulted in decreased (P<0.05) intestinal C20:1 and C20:5n3 content, and the decrease (P<0.05) in intestinal C20:3n6 and C24:1 content was observed in the BT-LPS piglets rather than in the FO-LPS piglets. Taken together, this study indicated that maternal consumption of fish oil protected breast-fed piglets against E. coli LPS-induced damage through reshaping of intestinal fatty acids profile, which sheds new light on the development of nutritional strategies to enhance the ability of young pigs to resist E. coli invasion.